Resiko Perubahan Tingkat Suku Bunga pada Bank Syariah dan Bank Konvensional dalam Kerangka Dual-Banking System: studi kasus Negara Indonesia - Ardiansyah, Vicki (Jurnal Aplikasi Manajemen, 2015)
The aim of this research is to know about the risks that Syariah Bank might faceregarding to the Interest Rate change in the Dual-Banking System in Indonesia by viewingthe impact of the Interest Rate change towards Third Party Funds (TPF) and also the level ofservice of Syariah Bank. This research uses monthly data from the Indonesia's BankingStatistic and correlation test to find out the correlation between the Interest Rate level andthe amount of TPF in the Conventional Bank and Syariah Bank and the Interest Rate Levelof Bank of Indonesia towards Syariah Bank TPF. Furthermore, this research uses regressiontest to see how big the impact from each variable is. The result of this research shows thatSyariah Bank in Indonesia (in the Dual-Banking System) is underwent of risks of the InterestRate change in both of the average rate of Conventional Bank or Bank of Indonesia.